Clinical profile of patients of pyrexia with hepatic dysfunction in a tertiary care hospital in Southern Rajasthan region of India - Mistry, Abhishek; Singhal, Yogesh Kumar; Gupta, Pankaj; Kumawat, D. C. (International Journal of Research in Medical Sciences, 2020)
Background: Pyrexia in association with hepatic dysfunction is commonly found in clinical practice with varied etiologies like malaria, dengue, typhoid, scrub typhus, viral hepatitis, etc. The liver is frequently involved in systemic infections, resulting in various types of abnormal liver function tests. It is very important to know the frequency and pattern of abnormal liver function tests in each infection for its appropriate management. Methods: A complete data of all the patients admitted in medicine wards and medicine ICU from January to December 2018 were studied. One hundred and ten patients with fever with abnormal liver function tests were interviewed and presenting complaints were noted. Demographic data such as age and sex were noted. These patients underwent a thorough general physical examination and systemic examination. The findings were noted on a predesigned and pretested proforma. The selected patient underwent blood investigations related to liver functions. Results: Most of the patients were of age group of 21 to 50 years (65 patients), 67 patients (60.91%) were males and 43 (39.09%) were females. Malaria (25.45%) and dengue (26.36%) were major etiologies. Hepatomegaly (46.36%), icterus in (45.45%) and splenomegaly (42.73%) were most common clinical signs. Conclusions: Present study will help clinicians to identify etiological factors and clinical picture in patients of pyrexia with hepatic dysfunction.